Development Of Multi-Controlled Floor Vacuum Cleaner Using RF Energy Harvesting - Indra, Win Adiyansyah; Chan, Jien Yang (Asian Research Publishing Network, 2019)
This paper investigated Multi-Controlled Floor Vacuum Cleaner power by Radio Frequency Energy Harvesting. Eco-friendly technology brings advance to this new era of technology. The energy consumption of electric is not environmentally friendly. To overcome the problem, implementing Radio Frequency Harvesting Energy to convert in to electric and power up electronic appliances. There are many automatic cleaner robot selling in the market nowadays. However the mostly use of infrared had a limitation in coverage; the robotic using Wi-Fi has a wider coverage. The uses of application also brings the coverage wider which can connect wherever the place have Wi-Fi connection or mobile data available. This benefits can brings more convenient to user can connect wherever they are. This project is started with an objective of develop a multi controlled floor vacuum cleaner using Wi-Fi. In order to make the system smart, ESP8266 Wi-Fi module used to have the internet connection. The prototype of project is developed by using Arduino Uno act as the main controller, L293D motor driver, and ultrasonic sensor. Besides that, Arduino IDE was used to write the program of the robot while Blynk apps use as a controller server. Through the project, this integrated design has performance for cleaning purpose in terms of user-friendly, convenient and eco-friendly.